International approaches to rural generalist medicine: a scoping review - Nicholas Schubert; Rebecca Evans; Kristine Battye; Tarun Sen Gupta; Sarah Larkins; Lachlan McIver (BMC, 2018)
Abstract Background Contemporary approaches to rural generalist medicine training and models of care are developing internationally as part of an integrated response to common challenges faced by rural and remote health services and policymakers (addressing health inequities, workforce shortages, service sustainability concerns). The aim of this study was to review the literature relevant to rural generalist medicine. Methods A scoping review was undertaken to answer the broad question 'What is documented on rural generalist medicine?' Literature from January 1988 to April 2017 was searched and, after final eligibility filtering (according to established inclusion and exclusion criteria), 102 articles in English language were included for final analysis. Results Included papers were analysed and categorised by geographic region, study design and subject themes. The majority of articles (80%) came from Australia/New Zealand and North America, reflecting the relative maturity of programmes supporting rural generalist medicine in those countries. The most common publication type was descriptive opinion pieces (37%), highlighting both a need and an opportunity to undertake and publish more systematic research in this area. Important themes emerging from the review were:DefinitionExisting pathways and programmesScope of practice and service modelsEnablers and barriers to recruitment and retentionReform recommendations There were some variations to, or criticisms of, the definition of rural generalist medicine as applied to this review, although this was only true of a small number of included articles. Across remaining themes, there were many similarities and consistent approaches to rural generalist medicine between countries, with some variations reflecting environmental context and programme maturity. This review identified recent literature from countries with emerging interest in rural generalist medicine in response to problematic rural health service delivery. Conclusions Supported, coordinated rural generalist medicine programmes are being established or developed in a number of countries as part of an integrated response to rural health and workforce concerns. Findings of this review highlight an opportunity to better share the development and evaluation of best practice models in rural generalist medicine.